Pendidikan Karakter Keluarga Perspektif Tafsir Tarbawi: Studi Penafsiran Ali Abdul Halim Mahmud - Muhammad Rizqi Fauzan Adhimah; Fejrian Yazdajird Iwanebel (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Character education is the provision given to an individual to shape their character or behavior, which needs to be implemented within the family. Family education is the inculcation of values or knowledge to the family, enveloped with religious teachings, thus creating a harmonious family through the cultivation of positive attitudes and behaviors derived from religious values developed within the family. The choice of this topic arises from the need for a deep understanding of Islamic teachings in the context of character education within the family. In the study of tafsir (Quranic exegesis), Ali Abdul Halim Mahmud has a work that interprets education,